Precoding algorithms for MIMO interference channels with channel mean feedback - Zhou Wen; Deng Dan (Dianzi Jishu Yingyong, 2018)
This paper studies the precoder design in multi-input multi-output(MIMO) interference channels, where it is assumed that interference channels have line-of-sight(LOS) paths and can be modeled as Rice fading channels，and the transmitter can only retrieve channel statistical information—channel mean matrices. Based on maximum signal-to-interference-plus-noise ratio(SINR) and signal-to-interference-plus-noise difference(SIND) criteria, two precoding methods are proposed. For the first method, an auxiliary variable is introduced so that the original non-convex problem is transformed into a convex one. Consequently, this problem is solved by the proposed bisection method that incorporates convex optimization softwares. For the second method, the original problem is decomposed into several sub-problems and the corresponding analytical solution is derived. By computer simulation, this paper demonstrates the convergence of the proposed algorithm and analyzes the effect of Rice factor on the system performance. The proposed methods are compared with a few classical transmission schemes and the results show the superiority of the proposed methods.